Small‐molecule nanoprodrug with high drug loading and EGFR, PI3K/AKT dual‐inhibiting properties for bladder cancer treatment - Li, Guoyin; Song, Zewen; Ru, Yi; Zhang, Jing; Luo, Lianxiang; Yang, Wei; Wu, Hao; Jin, Haibao; Bao, Xuanwen; Wei, Di; Yan, Zhao; Qu, Haijing; et al. (Exploration (Beijing, China), 2023)
Bladder cancer (BCa) is one of the most common malignancies worldwide. Although multiple efforts have been made, the 5‐year survival rate of patients with BCa remains unchanged in recent years. Overexpression of the epidermal growth factor receptor (EGFR) is found in ≈74% of BCa tissue specimens; however, current EGFR‐based targeted therapies show little benefit for BCa patients, as the EGFR downstream pathways appear to be circumvented by other receptor tyrosine kinases (RTKs). In this study, two natural products are identified, namely triptolide (TPL) and hesperidin (HSP), that target and inhibit the EGFR and its downstream PI3K/AKT pathway in BCa. To synergistically combine triptolide and hesperidin, a succinic acid linker was employed to conjugate them and formed an amphiphilic TPL‐HSP EGFR‐targeting prodrug (THE), which further self‐assembled to generate nanoparticles (THE NPs). These NPs allowed the EGFR‐targeted delivery of the triptolide and hesperidin, and simultaneous inhibition of the EGFR and PI3K/AKT both in vitro and in vivo. This study provides a promising EGFR‐targeted delivery approach with the dual inhibition of the EGFR and PI3K/AKT, while also exhibiting a high drug loading and low toxicity. Our formulation may be a suitable option to deliver natural products for BCa treatment by EGFR‐targeted therapy.